Nano-ZnO Catalyzed Multicomponent One-Pot Synthesis of Novel Spiro(indoline-pyranodioxine) Derivatives - Harshita Sachdeva; Rekha Saroj; Diksha Dwivedi (The Scientific World Journal)
A simple catalytic protocol for the synthesis of novel spiro[indoline-pyranodioxine] derivatives has been developed using ZnO nanoparticle as an efficient, green, and reusable catalyst. The derivatives are obtained in moderate to excellent yield by one-pot three-component reaction of an isatin, malononitrile/ethylcyanoacetate, and 2,2-dimethyl-1,3-dioxane-4,6-dione in absolute ethanol under conventional heating and microwave irradiation. The catalyst was recovered by filtration from the reaction mixture and reused during five consecutive runs without any apparent loss of activity for the same reaction. The mild reaction conditions and recyclability of the catalyst make it environmentally benign synthetic procedure.